MANAJEMEN PEMASARAN JASA PENDIDIKAN PERSPEKTIF AL-QUR’AN - Ahmad Zain Sarnoto; Lukmanul Hakim (Jurnal Kajian Agama Hukum dan Pendidikan Islam (KAHPI), 2023)
Marketing of educational services has become a hot issue and a challenge for educational institution managers, due to increasingly competitive competition between educational institutions. This condition encourages educational institutions to make maximum efforts in marketing educational services. This study tries to examine the concept of marketing educational services from the perspective of the Koran, so that it is hoped that it can provide Qur'anic values in the practice of marketing educational services.Referring to the concept of relational marketing, this study explores the term da'wah as a marketing term in the Qur'an. Marketing management of educational services from the perspective of the Koran is described in three parts. First, the reformulation of the marketing management concept of educational services using the service marketing paradigm from the Al-Qur'an perspective. Second, the marketing of educational services uses the bil wisdom, mauidhah hasanah, and al jidal billati hiya ahsan methods. Third, service marketing orientation and model, implemented in a holistic spiritual based on religious values. Kata Kunci : Manajemen Pemasaran, Jasa Pendidikan, Relational Marketing